Analysis and design of a web-based integrated inventory information system using the PIECES framework: A case study of PT. Asia Persada Nusantara - Uya Asy Syuura Anandri; Ilyas Ilyas (Privietlab, 2026)
This study aims to analyze and develop a systematic or analytical web-based integrated inventory information system for PT. Asia Persada Nusantara, analytical used by PIECES framework. Based on a case-study approach, both with the SDLC methodology with a prototyping model, the requisite data were acquired by a complete review of documents and by conducting interviews with stakeholders. The Object Oriented Tool Development was modeled using the Unified Modeling Language (UML) to define the functional and non-functional requirements. The resultant design captures role-based authentication, stock reservation systems, processing of goods receipts including the processing of delivery notes, keeping of discrepancies, payment and reconciliation systems, and role-based audit trails as a way of enforcing operational control. The shared schema of the relational database using ERD supports the atomic transactions of the key turbines (reservation, transaction creation, commitment) and helps to reduce the risk of overselling and information inconsistency. It is proposed that a staged implementation plan (Minimum Viable Product) should be used with an initial focus on real-time inventory and reservation logic to achieve more immediate operations payoffs. The indicators of future improvement in stock accuracy and process efficiency are stated by impact assessment, whereas the real benefits depend on piloting testing, initial data quality, and organizational readiness. This research provides a technical map that is suitable for developing prototypes and validating them empirically.